Role of CD36 in cancer progression, stemness, and targeting - Guerrero-Rodríguez, Sandra L.; Mata-Cruz, Cecilia; Pérez-Tapia, Sonia M.; Velasco-Velázquez, Marco A. (Frontiers in Cell and Developmental Biology, 2022)
CD36 is highly expressed in diverse tumor types and its expression correlates with advanced stages, poor prognosis, and reduced survival. In cancer cells, CD36: i) increases fatty acid uptake, reprogramming lipid metabolism; ii) favors cancer cell proliferation, and iii) promotes epithelial-mesenchymal transition. Furthermore, CD36 expression correlates with cancer stem cell markers and CD36+ cancer cells display increased stemness functional properties, including clonogenicity, chemo- and radioresistance, and metastasis-initiating capability, suggesting CD36 as a marker of the cancer stem cell population. Thus, CD36 has been pointed as a potential therapeutic target in cancer. At present, at least three different types of molecules have been developed for reducing CD36-mediated functions: blocking monoclonal antibodies, small-molecule inhibitors, and compounds that knock-down CD36 expression. Herein, we review the role of CD36 in cancer progression, its participation in stemness control, as well as the efficacy of reported CD36 inhibitors in cancer cell cultures and animal models. Overall, the evidence compiled points that CD36 is a valid target for the development of new anti-cancer therapies.